Предмет: Алгебра, автор: hhhhhhh0

хотя бы несколько,плииииииз)))

Приложения:

Ответы

Автор ответа: Аноним
1

1) (5+b) * (b-5) - b² = (b+5) * (b-5) - b² = b² - 25 - b² = -25

2) c² + (9-c) * (9+c) = c² + 81 - c² = 81

3) (\frac{1}{3} -z) * (\frac{1}{3} +z) - \frac{1}{9} = \frac{1}{9} -z^{2}-\frac{1}{9} = -z^{2}

4) -\frac{16}{49}+(\frac{4}{7} -d) * (d+\frac{4}{7}) = -\frac{16}{49}+(\frac{4}{7} -d) * (\frac{4}{7} +d) = -\frac{16}{49} + \frac{16}{49} -d^{2} = -d^{2}

5) (0,9-a) * (a+0,9) - a * (1+a) = (0,9 - a) * (0,9 + a) - a - a² = 0,9² - a² - a - a² = (\frac{9}{10})^{2} -a^{2}-a-a^{2}  = \frac{81}{100} -2a^{2} -a

6) k * (5-k) + (1,2+k) * (k-1,2) = 5k - k² + (k+1,2) * (k-1,2) = 5k - k² + k² - 1,2² = 5k -(\frac{6}{5})^{2} = 5k-\frac{36}{25}

Похожие вопросы
Предмет: Математика, автор: housepersick